Effect of incorporation of crop residues on a maize-groundnut sequence in the humid tropics. II. soil physical and chemical properties - Mubarak, A.R.; Rosenani, A.B.; Anuar, A.R.; Zauyah, D. Siti (Informa UK Limited, 2003)
A two-year study (1997-1999) was conducted on a sandy clay loam (Typic Paleudult) at the experimental farm of the Universiti Putra to determine the effects of application of crop residues on changes of some soil properties in a maize (Zea mays L.)-groundnut (Arachis hypogaea) crop rotation system. Five crops of a rotation of sweet corn-groundnut-sweet corn-groundnut-sweet corn were sown with three treatments: recommended inorganic fertilizer [nitrogen (N), phosphorus (P), and potassium (K)] with crop residue (T1), recommended inorganic fertilizer without crop residues (T2) or one-half of the recommended inorganic fertilizer with crop residues combined with 10 t ha-1 of chicken manure (T3). Soil organic carbon (OC), soil water content and soil bulk density were not significantly changed. Application of crop residues for two years increased cation exchange capacity (CEC) whereas supplementing crop residues with CM had significantly increased soil pH of the topsoil. Phosphorous in manure treatment had moved down the soil profile, which might cause eutriphication of under ground water, particularly during the rainy season. Based on this work, incorporation of crop residues could be a beneficial practice for improving the fertility of acid soils.